Severe allergic dysregulation due to a gain of function mutation in the transcription factor STAT6 - BARIŞ, SAFA; YÜCELTEN, AYŞE DENİZ; BOZKURTLAR, EMİNE; CİNEL, ZELİHA LEYLA; AYDINER, ELİF; ÖZEN, AHMET OĞUZHAN (My University, 2023)
Background: Inborn errors of immunity have been implicated in causing immune dysregulation, including allergic diseases. STAT6 is a key regulator of allergic responses. Objectives: This study sought to characterize a novel gain-of-function STAT6 mutation identified in a child with severe allergic manifestations. Methods: Whole-exome and targeted gene sequencing, lymphocyte characterization, and molecular and functional analyses of mutated STAT6 were performed. Results: This study reports a child with a missense mutation in the DNA binding domain of STAT6 (c.1114G>A, p.E372K) who presented with severe atopic dermatitis, eosinophilia, and elevated IgE. Naive lymphocytes from the affected patient displayed increased TH2- and suppressed TH1- and TH17-cell responses. The mutation augmented both basal and cytokine-induced STAT6 phosphorylation without affecting dephosphorylation kinetics. Treatment with the Janus kinase 1/2 inhibitor ruxolitinib reversed STAT6 hyperresponsiveness to IL-4, normalized TH1 and TH17 cells, suppressed the eosinophilia, and improved the patient\"s atopic dermatitis. Conclusions: This study identified a novel inborn error of immunity due to a STAT6 gain-of-function mutation that gave rise to severe allergic dysregulation. Janus kinase inhibitor therapy could represent an effective targeted treatment for this disorder.
Keywords: Tıp; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; İmmünoloji; ALERJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; IMMUNOLOGY; ALLERGY; İmmünoloji ve Alerji; Immunology and Allergy; Immunology; gain-of-function mutation; Inborn errors of immunity; Jakinibs; Janus kinase inhibitors; primary atopic disorders; STAT6